Membangun Sikap Unitas dalam Diversitas Di Pesantren Sebagai Bentuk Perlawanan Terhadap Intoleransi (Studi Fenomenologis Terhadap Pondok Pesantren Darul Faqih Di Krajan Malang - Esserey, Sepustinus (Perspektif, 2023)
In this paper the author pays attention to the theme “Building an Attitude of Unity in Diversity in Islamic Boarding Schools as a Form of Resistance against Intolerant Attitudes” using Alfred Schutz’s social-phenomenological perspec[1]tive. The method of this research is using interview with three sources from the “Darul Faqih” Islamic boarding school in Malang. From the results of the research carried out, the author can argue that Building an Attitude of Unity in Diversity at the “Darul Faqih” Islamic Boarding School has a relationship with Alfred Schutz’s social phenomenology which related to three of the six basic characters of The Life World. Pesantren is not only a place to deepen the Islamic religion but also as a place to build an attitude of tolerance. Instill the value of wide-awakened, openness to reality as it is (reality) and build relationships with others (intersubjectivity). Tolerance is built by fostering a sense of brotherhood (ukhuwah) which is explained into three: brotherhood between fellow Muslims (ukhuwah islamiah), brotherhood among fellow coun[1]trymen and fellow countrymen (ukhuwah watoniah) and finally brotherhood between fellow humans (ukhuwah basariah). Everything is realized in Islamic boarding schools through awareness and relationships.